Kalimate-Associated Gastric Ulcer - Tae Yeong Lee; Jong Kyu Park; Sang Jin Lee; Byeong-Joo Noh (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Kalimate (calcium polystyrene sulfonate) is a cation-exchange resin commonly used in clinical practice to treat hyperkalemia. However, Kalimate has been demonstrated to also cause serious gastrointestinal injuries, such as colonic necrosis, ulcerations, and perforations, in a subset of patients with chronic renal failure; these cases have been reported with and without the administration of hypertonic sorbitol. These lesions usually occur in the large or small intestine; lesions occurring in the stomach are rarely reported. We present the case of a 62-year-old woman with very large Kalimate-induced gastric ulcers that were mistaken for advanced gastric cancer in patients with chronic renal failure who had been taking Kalimate for the previous 3 months. The patient was successfully treated by discontinuing Kalimate and initiating a proton pump inhibitor.